'From Time Into Eternity': Schelling on Intellectual Intuition. Issue 4 (22nd February 2023) - Bruno, G. Anthony
Abstract: Throughout his career, Schelling assigns knowledge of the absolute first principle of philosophy to intellectual intuition. Schelling's doctrine of intellectual intuition raises two important questions for interpreters. First, given that his doctrine undergoes several changes before and after his identity philosophy, to what extent can he be said to "hold onto" the same "sense" of it by the 1830s, as he claims? Second, given that his doctrine of intellectual intuition restricts absolute idealism to what he calls a "science of reason", which he says cannot prove the absolute's existence, what other doctrine does he require in order to prove this? I will answer these questions by tracing the shifts in Schelling's doctrine of intellectual intuition from the 1790s to the 1830s and drawing out its evolving methodological role within his science of intelligibility.